Application of Artificial Intelligence (Neural Networks) in Education - Zakaryan, Arman (Զանգակ հրատ.)
This article focuses on the use of artificial intelligence in the educational environment. We consider the latest technology, which already plays a huge role for both teachers and students. Currently, there are many systems for the development of training systems, among which artificial neural networks occupy a substantial place. The article presents an example of the use of artificial neural networks, which can play a significant role in developing educational systems.
Keywords: Pedagogy